Effective stiffness of corrugated plate - Sheshenin, Sergey Vladimirovich; Hodos, Olga Alexandrovna (Computational Continuum Mechanics, 2011)
This paper presents a homogenization technique applied to periodic in-plane corrugated plates. The developed method allows the calculation of the tension stiffness, the bending stiffness and the tension-bending coupled stiffness. This problem is computationally difficult because the stiffness values differ by several orders of magnitude in one and the same plate. The use of the model permits a substantial saving in computing resources. For the stress-strain analysis of the plate in a first approximation, it is sufficient to compute all the effective stiffness values for a periodic cell and then to use these values in the solution of the flat plate bending problem. The accuracy of the solution depends on the character of the problem. For a smoothly varying transverse load and a large-size plate, the accuracy is high enough. The validity of the computer program developed for calculating the effective stiffness of corrugated plates has been verified.